Does Nasal Septum Deviation with Different Locations and Different Angular Features Affect Maxillary Sinus Volumes? - Avcı, Deniz; Tiryaki, Şaban (ENT Updates, 2021)
Objective: The aim of this study was to investigate the isolated effect of moderateto- severe, lower, middle, and upper nasal septum deviation (NSD) and NSD angle on maxillary sinus volume (MSV). Methods: The retrospective study included 94 NSD patients (mean age, 27.95 ± 12.01 years). NSD diagnosis and the measurements of NSD angle and MSV were performed using paranasal sinus computed tomography (PNS CT). The NSD angle was divided into 2 groups as moderate (≤9 to <15) and severe (≥15) according to its degree on PNS CT. Each group was divided into 3 subgroups as lower, middle, and upper NSD based on the localization of NSD. MSV was measured both on the affected and unaffected sides using volume-measuring software. Results: Mean MSV was 13.76 ± 4.81 mL on the affected side as opposed to 14.46 ± 4.95 mL on the unaffected side in 94 patients (P = .03). The increase in the NSD angle had a significant effect on both MSVs (P = .037, for severe NSD). No significant difference was found between the side with lower, middle, or upper NSD and the contralateral side in terms of MSV (P > .05). Conclusion: We consider that NSD and an angular increase in NSD may play a role in MSV, while NSDs in different locations do not affect MSVs.